MIMO ANTENNA ARRAY WITH DIRECTIONAL DIAGRAM SPREAD FOR 5G SMARTPHONES - MISHAN, Viktor; KARPOVA, Lesia; LOBACHOVA, Inna (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Multiple-input/multiple-output technology can exponentially increase the data transfer rate and spectrum efficiency without any need of increasing the transmission power and bandwidth. It is the most promising technology to be used in the upcoming 5G communications. To be more accurate, the fourth generation smartphones are set to use the long-term evolution MIMO technology and operate in multi-bands.  Therefore, MIMO antennas are to use in future portable devices such as mobile handsets and tablets. A new multiple-input/multiple-output (MIMO) antenna design is introduced for future smartphones. The proposed design contains four pairs of double-fed circular-ring resonators located at different edges of the smartphone printed circuit board (PCB) with an FR-4 substrate and a dimension of 75 × 150 mm2. The antenna elements are fed by 50-Ohm microstriplines and provide polarisation and radiation pattern diversity function due to the orthogonal placement of their feed lines. By inserting a rectangular slot under each microstrip feed-line, the mutual coupling characteristic of the antenna ports is reduced. A good frequency bandwidth (S11 ≤ − 10 dB) of 3.3–3.9 GHz has been obtained for the smartphone antenna array. Nevertheless, for S11 ≤ −6 dB, this value is 3.1–4.3 GHz. More than 3 dB realised gain and 80% total efficiency are achieved for the single element radiator. The design provides not only sufficient radiation coverage supporting different sides of the mainboard but also the polarisation diversity. In addition, sufficient properties are obtained in the vicinity of human-hand/human-head. The proposed MIMO antenna design is also capable to generate dual- or multi-band function. Moreover, a new and compact phased array millimeter-wave (mm-wave) antenna design with end-fire radiation beams is introduced which can be easily integrated into smartphones.
Keywords: multiple-input/multiple-output MIMO antenna; beam pattern; phased array; polarization; bandwidth; 5G smartphones